UJI AKTIVITAS ANTIOKSIDAN SENYAWA PIRAZOLIN 3-(2- METOKSI-FENIL)-5-NAFTALEN-1-IL-4,5-DIHIDRO-1H-PIRAZOL - Nurlaili, -; Jasril, -; Teruna, Hilwan Yuda (Fakultas MIPA dan Kesehatan Universitas Muhammadiyah Riau, 2018)
Pyrazoline compounds are reported to have many useful biological activities such as antimicrobials, antihyperglycemia, antioxidants, anti-inflammatory, anticancer and anticonvulsants. The pyrazoline analogues of 3- (2-methoxy-phenyl) -5-naphthalene-1-yl-4,5-dihydro-1H-pyrazol were synthesized usingglacial acetic acid as catalyst and assisted by microwave irradiation. The structures of the compounds were obtainedby UV, IR and HRMS spectroscopy data. Antioxidant activity test using DPPH method showed that pyrazoline compound had IC50 value of 27.41 Î¼g/mL.